Development of gluten-free functional snack bar for gluten intolerant population by utilizing pseudocereals and dates - Ahada Sabeel V; Praveen Kumar Dubey; Swarup Roy (Food Chemistry Advances)
This study focuses on developing a functional snack bar incorporating nutrient-dense ingredients such as quinoa, amaranth, dates, raisins, dried figs, and roasted peanuts. The bars were analyzed for proximate composition, nutraceutical characteristics, color, texture, sensory attributes, and shelf-life stability. Proximate analysis showed protein content from 12.16±0.05% and 13.36±0.11%. and fat content between 14.16±0.05% and 13.22±0.03%. Antioxidant activity ranged between 38.00±0.45% and 36.34±0.32%, with high phenolic (124.66±0.11–150.18±0.18 mg GAE/g) and flavonoid (25.94±0.42–12.40±0.45 mg QE/g) contents. Fourier-transform infrared spectroscopy (FTIR) analysis confirmed the presence of various functional groups associated with the ingredients without any new groups. Scanning electron microscopy (SEM) images revealed varying proportions of popped amaranth and quinoa flour, which significantly influenced the matrix structure. Sensory evaluation favoured the formulation with 10% popped amaranth, 20% quinoa, and 40% dates, scoring 8.43±0.45. Shelf-life studies indicated good stability over 28 days. Cost analysis revealed affordability compared to market samples, suggesting potential for scaling up production to meet market demand.